Perbandingan Karakteristik Infused Water (Apel + Jeruk + Kiwi) Berdasarkan Suhu dan Waktu - Duta Warasita; Eliska Eliska (Prodi Kesehatan Masyarakat FKM UIN Sumatera Utara Medan, 2022)
Infused water is a healthy drink that contains minerals and vitamins obtained from a mixture of ingredients in infused water, such as fruit and spices. Infused water can be used as an alternative for people who have difficulty consuming only mineral water. Infused water has a variety of additional flavors in mineral water so that people who consume it do not get bored with the taste of mineral water.The purpose of this study was to compare the characteristics of infused water stored at room temperature (310C) and refrigerator temperature (40C) and how long the infused water can last at room temperature and refrigerator temperature. This research method is experimental, with temperature and storage time factors consisting of 6, 12, 24, 48, and 72 hours, then organoleptic tests are carried out. The results obtained based on a good temperature and time to make infused water are 48 hours or two days at a refrigerator temperature of 40C and 12 hours at a temperature of 310C and 40C, for the taste and aroma of good quality infused water is at a temperature of 40C. Suggestions in making infused water, the longest storage is 2 days without refill, if there is a refill, you should use infused 12 hours